2017
DOI: 10.1007/s11547-017-0778-y
|View full text |Cite
|
Sign up to set email alerts
|

Which MR sequences should we use for the reliable detection and localization of bone marrow edema in spondyloarthritis?

Abstract: confidence in detection (p < 0.001) and localization (p < 0.001) of sacroiliitis; no significant difference occurred between the multiplanar unenhanced and enhanced methods (p = 0.405 and p = 1.00, respectively, for detection and localization). A statistically significant difference between the distributions of certain and uncertain rating for detection based on the size and signal intensity of each lesion emerged (p = 0.006 and p < 0.001, respectively), whereas no statistically significant difference occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…No new surrounding edema was observed in the enhanced images, and there was no significant difference in the incidence of surrounding edema between the plain scan and the enhanced scan. These results were consistent with those reported by Giraudo et al [19]. The boundaries of surrounding edema and lesions are clearer in contrast enhanced than in non-contrast enhanced images, as shown by Liu et al [20], who reported that enhanced MRI imaging can depict osteoid osteomas with greater accuracy than non-enhanced MRI, facilitating the detection of the size and morphology of the lesions.…”
Section: Discussionsupporting
confidence: 92%
“…No new surrounding edema was observed in the enhanced images, and there was no significant difference in the incidence of surrounding edema between the plain scan and the enhanced scan. These results were consistent with those reported by Giraudo et al [19]. The boundaries of surrounding edema and lesions are clearer in contrast enhanced than in non-contrast enhanced images, as shown by Liu et al [20], who reported that enhanced MRI imaging can depict osteoid osteomas with greater accuracy than non-enhanced MRI, facilitating the detection of the size and morphology of the lesions.…”
Section: Discussionsupporting
confidence: 92%
“…We know that MRI is the gold standard diagnostic tool for the evaluation of joint soft tissue, thanks to its high intrinsic contrast and spatial resolution with multiparametric information. [13][14][15][16][17][18][19][20] The main limitation of cross-sectional modalities, and particularly MRI, is the limited imaging in the supine position on most scanners. Several previous studies proposed the use of axial loads to mimic gravity load on joints during traditional supine scanning.…”
Section: Weight-bearing Kneementioning
confidence: 99%